AKAP complex regulates Ca2+ re-uptake into heart sarcoplasmic reticulum. - Lygren, B; Carlson, C; Santamaria, K; Lissandron, V; McSorley, T; Litzenberg, J; Lorenz, D; Wiesner, B; Rosenthal, W; Zaccolo, M; Taskén, K; Klussmann, E (2007)
The beta-adrenergic receptor/cyclic AMP/protein kinase A (PKA) signalling pathway regulates heart rate and contractility. Here, we identified a supramolecular complex consisting of the sarcoplasmic reticulum Ca(2+)-ATPase (SERCA2), its negative regulator phospholamban (PLN), the A-kinase anchoring protein AKAP18delta and PKA. We show that AKAP18delta acts as a scaffold that coordinates PKA phosphorylation of PLN and the adrenergic effect on Ca(2+) re-uptake. Inhibition of the compartmentalization of this cAMP signalling complex by specific molecular disruptors interferes with the phosphorylation of PLN. This prevents the subsequent release of PLN from SERCA2, thereby affecting the Ca(2+) re-uptake into the sarcoplasmic reticulum induced by adrenergic stimuli.